Drogi awansu chłopów polskich w świetle wskaźników antropologicznych - Welon, Zygmunt (Polskie Towarzystwo Antropologiczne, 1992)
The hypothesis that the rise was achieved mainly owing to the leaving the farming or by moving to towns, was proved. Military conscripts (20,085) were divided into 10 appropriate social groups. Social status was measured by use of stature, educational level and health cathegory of conscripts.
The social rise of countrypeople in poland in the light of the anthropological measures